West Greenlandic antipassive - Schmidt, Bodil Kappel (Universitetet i Tromsø, 2003)
In special issue: Proceedings of SCL 19 On the basis of syntactic and morphological evidence from West Greenlandic (WG) antipassive (AP) constructions, I argue against the view that the AP affix is nominal. The fact that the transitivizing and the antipassive affixes in a number of verbs are in complementary distribution, leads me to conclude that they both realize a light verb, transitivizing v, one on the ERG-NOM pattern, the other on the NOM-ACC pattern. Nominalization facts of the two clause types indicate their syntactic structure, with possible implications for the semantic interpretation of the object and the position of the ergative subject.